Potential targets and treatments affect oxidative stress in gliomas: An overview of molecular mechanisms - Liu, Shiyu; Dong, Lihua; Shi, Weiyan; Zheng, Zhuangzhuang; Liu, Zijing; Meng, Lingbin; Xin, Ying; Jiang, Xin (Frontiers in Pharmacology, 2022)
Oxidative stress refers to the imbalance between oxidation and antioxidant activity in the body. Oxygen is reduced by electrons as part of normal metabolism leading to the formation of various reactive oxygen species (ROS). ROS are the main cause of oxidative stress and can be assessed through direct detection. Oxidative stress is a double-edged phenomenon in that it has protective mechanisms that help to destroy bacteria and pathogens, however, increased ROS accumulation can lead to host cell apoptosis and damage. Glioma is one of the most common malignant tumors of the central nervous system and is characterized by changes in the redox state. Therapeutic regimens still encounter multiple obstacles and challenges. Glioma occurrence is related to increased free radical levels and decreased antioxidant defense responses. Oxidative stress is particularly important in the pathogenesis of gliomas, indicating that antioxidant therapy may be a means of treating tumors. This review evaluates oxidative stress and its effects on gliomas, describes the potential targets and therapeutic drugs in detail, and clarifies the effects of radiotherapy and chemotherapy on oxidative stress. The overall aim is to have the ability to treat gliomas with optimal clinical benefit using a more precise targeted therapeutic approach.